Direct evidence for the adaptive role of copy number variation on antifolate susceptibility in Plasmodium falciparum. Issue 4 (24th April 2013) - Heinberg, Adina; Siu, Edwin; Stern, Chaya; Lawrence, Elizabeth A.; Ferdig, Michael T.; Deitsch, Kirk W.; Kirkman, Laura A.
Summary Resistance to antimalarials targeting the folate pathway is widespread. GTP‐cyclohydrolase (gch1), the first enzyme in this pathway, exhibits extensive copy number variation (CN) in parasite isolates from areas with a history of longstanding antifolate use. Increased CN of gch1 is associated with a greater number of point mutations in enzymes targeted by the antifolates, pyrimethamine and sulphadoxine. While these observations suggest that increases in gch1 CN are an adaptation to drug pressure, changes in CN have not been experimentally demonstrated to directly alter drug susceptibility. To determine if changes in gch1 expression alone modify pyrimethamine sensitivity, we manipulated gch1 CN in several parasite lines to test the effect on drug sensitivity. We report that increases in gch1 CN alter pyrimethamine resistance in most parasites lines. However we find evidence of a detrimental effect of very high levels of gch1 overexpression in parasite lines with high endogenous levels of gch1 expression, revealing the importance of maintaining balance in the folate pathway and implicating changes in gch1 expression in preserving proper metabolic flux. This work expands our understanding of parasite adaptation to drug pressure and provides a possible mechanism for how specific mutations become fixed within parasite populations.